From professionalism to commercialism in healthcare: a phenomenological study - Muhammad Hanif Malik; Usman Mahboob (Journal of the Pakistan Medical Association, 2020)
Objective: To explore the perceptions of doctors holding dual jobs regarding professionalism in public and private healthcare sectors. Methods: The qualitative phenomenological study was conducted from January to June 2016 in a tertiary care teaching hospital affiliated with Sheikh Zayed Medical College, Rahim Yar Khan, Pakistan, and comprised 10 doctors holding dual jobs. Data was collected through video-recorded interviews which were transcribed verbatim and analysed for themes using interpretative phenomenological analysis. Results: There were 10 doctors in the study. Monetary benefit was the main motive behind holding dual jobs. Contented and internally motivated practitioners with faith in Almighty and a sense of accountability before Him were likely to behave much more professionally, and a virtue-based medical education could play a vital role in this regard. Conclusion: Overall lack of faith and internal motivation has shifted the focus of sustenance to material resources. Continuous...